Representasi Kesetiaan Pada Lirik Lagu “Penjaga Hati” Karya Nadhif Basalamah - Larasati, Rasyikah Dzihni (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the representation of loyalty in the lyrics of Penjaga Hati by Nadhif Basalamah using Roland Barthes' semiotic approach. The song was selected because of its popularity among young people and the moral values embedded in its lyrics. This research employed a qualitative method with semiotic analysis through Barthes’ three levels of signification: denotation, connotation, and myth. The findings reveal that, at the denotative level, the lyrics depict a promise to remain present and protect a loved one. At the connotative level, the lyrics represent loyalty as a symbol of ideal love and emotional commitment. At the mythological level, the song constructs the ideology that loyalty is the fundamental foundation of true love in popular culture. The study concludes that music, particularly song lyrics, serves not only as entertainment but also as a medium of mass communication that conveys moral and cultural values to a wide audience. This research is expected to contribute theoretically to the fields of mass communication and popular culture studies, while also providing practical insights for the public to better appreciate music as a medium for communicating moral values.